Diogenes Laertius and the Apostolic Succession - Brent, Allen (The journal of ecclesiastical history, 1993)
The cultural and historical location of the concept of ςιαςοϰή in second century claims about the apostolic succession has been widely debated. In England, under the influence of Ehrhardt, the term is generally taken to be used by analogy with the sacerdotal succession of Jewish high priests, and to derive from the influence of James the Just on Jewish Christianity. In Germany, on the other hand, following Campenhausen, ςιαςοϰή has been understood in terms of continuity of doctrine, in which references to James in the sources are regarded as pure legend constructed to make the point of such continuity in a picturesque way. Both Ehrhardt and Campenhausen, and their respective followers, regard the ςιαςοχή of teachers in the literature of the Hellenistic philosophical schools as quite incidental, without any close relation to the Christian usage. In this article I will argue the contrary, that there are in fact integral connections between the Hellenistic literature of the philosophical successions, and the development of the idea of the apostolic succession in the late second century, where perhaps the true origin of the Christian concept is to be found.